Receiving the initial Down syndrome diagnosis: a comparison of prenatal and postnatal parent group experiences - Goff, Briana S.; Springer, Nicole; Foote, Laura Cline; Frantz, Courtney; Peak, Madison; Tracy, Courtney; Veh, Taylor; Bentley, Gail E.; Cross, Kayli A. (My University, 2013)
This study explored the preliminary experiences of parents upon learning of their child's diagnosis of Down syndrome. Qualitative data from a web-based, national survey were analyzed based on two groups: prenatal (n  =  46) or postnatal (n  =  115) diagnosis. Three primary categories emerged from the data analysis: prenatal screening/testing decisions by parents, the adjustment process for parents, and postdiagnosis resources and support for parents. Participants' rationale behind pursuing testing ranged from wanting to be better prepared to not pursuing testing because it was not a factor in continuing the pregnancy. Participant reactions to the diagnosis involved a range of intense preliminary emotions; participants described their extreme grief and loss experience at the initial news of the diagnosis, which also was ambiguous in nature and required differing timelines of adjustment. Finally, participants described experiences with medical professionals, information/education, and faith/religion as resources and areas of support, although not all were described as positive in nature. Participants in both groups identified having negative experiences with medical professionals during the diagnosis process. The results indicated the importance of these early experiences for parents of children with Down syndrome and emphasize providing effective education, resources, and practical information from reliable sources.
Keywords: Down syndrome; Parenting; Prenatal diagnosis; Postnatal diagnosis; Qualitative research